PERANAN INCOME SMOOTHING DALAM LAPORAN KEUANGAN PERUSAHAAN MENURUT EKONOMI ISLAM - SIREGAR, BUDI GAUTAMA (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
The problem of this research is how the role of income smoothing in the financial statements according to Islamic economics . Furthermore, this study aims to determine the role of income smoothing in the financial statements according to Islamic economics . The theory behind this research is the theory of agency ( agency theory ) which states that the earnings management practices are influenced by conflicts of interest between principal and agent management that arises when each party seeks to achieve or maintain a desired level of prosperity respectively .The method used in this study is a literature method by analyzing the literature , articles , research results . In various literature review found that the normalized earnings Income smoothing is done intentionally to achieve a particular trend or level of profit motivation that encourages income smoothing is to improve relations with creditors , investors, and employees , as well as leveling the business cycle through a psychological process .Reported income smoothing can be defined as a deliberate attempt to flatten and mengfluktuasikan sehinnga profit level at the present time is deemed normal for a company. In Islam this income smoothing activity seems contrary to the rules of fiqh muamalah , which contain elements of fraud ( tadlis ) and uncertainty ( gharar ) because there are those who hide information to the other party (unknown to one party ) with the intent to deceive others for his ignorance about that information . And if this action is proven , then it is forbidden in Islam , because it violates the principle of "an  taraaddin minkum" ( both pleasure).